An unexpected Streptococcus pneumoniae strain. (June 2014) - Cenderello, Giovanni; Pontali, Emanuele; Torresin, Augusta; Milano, Giulia; Ansaldi, Filippo; Feasi, Marcello; Usiglio, David; Mori, Marco; Icardi, Giancarlo; Cassola, Giovanni
Abstract : This clinical driven report describes the unexpected detection of a multidrug resistant (MDR) Streptococcus pneumoniae strain. Italy is usually considered a country characterized by a low prevalence of MDR S. pneumoniae . We describe the occurrence of bacterial meningitis sustained by a MDR S. pneumoniae strain in Italy. The first-line treatment was started with ceftriaxone and dexamethasone, but after the identification of such a resistant strain a second-line regimen was needed. The new regimen was chosen on both susceptibility and pharmacokinetic criteria. Linezolid and levofloxacin were started and a dramatic improvement was observed. A more sensitive anamnesis revealed some elements known to be associated to a MDR S. pneumoniae occurrence (immunesuppression, former antibiotic therapy). So this case should pinpoint our attention on risk factors of MDR for a careful choice of antibiotic therapy in serious pneumococcal infections.